Virulensi Isolat Rice tungro virus dari Beberapa Daerah Endemis Tungro di Indonesia - Suprihanto Suprihanto; Endang Nurhayati; Jumanto Harjosudarmo (Jurnal Fitopatologi Indonesia, 2013)
The research was conducted to distinguish the virulence of Rice tungro virus (RTV) isolates from several tungro disease endemic areas in Indonesia based on their response in differential cultivars of rice. Eight isolates of RTV were collected from several tungro endemic regions in Indonesia i.e. Bali (Denpasar), South Kalimantan (Tanah Laut), South Sulawesi (Lanrang), West Java (Subang and Bogor), Central Java (Solo), East Java (Jember), and West Nusa Tenggara (Mataram). The isolates were maintained on TN1 rice cultivar in greenhouse by successive transfers via Nephotettix virescens. Each isolate was subsequently passed on to FK135 and TN1 rice cultivars. Four week after inoculation, plants responses were observed to compare their symptom and infectivity on the differential cultivars. The results showed that the level of virulence of RTV isolate from tungro disease endemic areas in Indonesia can be classified into 3 levels. The highest virulence were RTV isolates from West Jawa, the moderate level of virulence were RTV isolates from East Java, South Kalimantan, South Sulawesi, and West Nusa Tenggara, the low level of virulence were RTV isolates from Bali and Central Java.Key words: differential cultivar, Nephotettix virescens, rice, tungro diseases